Oxidation Mechanism of Biomedical Titanium Alloy Surface and Experiment. (13th August 2020) - Ma, Kai; Zhang, Rui; Sun, Junlong; Liu, Changxia
Abstract : The biological activity, biocompatibility, and corrosion resistance of implants depend primarily on titanium dioxide (TiO2 ) film on biomedical titanium alloy (Ti6Al4V). This research is aimed at getting an ideal temperature range for forming a dense titanium dioxide (TiO2 ) film during titanium alloy cutting. This article is based on Gibbs free energy, entropy changes, and oxygen partial pressure equations to perform thermodynamic calculations on the oxidation reaction of titanium alloys, studies the oxidation reaction history of titanium alloys, and analyzes the formation conditions of titanium dioxide. The heat oxidation experiment was carried out. The chemical composition was analyzed with an energy dispersive spectrometer (EDS). The results revealed that titanium dioxide (TiO2 ) is the main reaction product on the surface below 900°C. Excellent porous oxidation films can be obtained between 670°C and 750°C, which is helpful to improve the bioactivity and osseointegration of implants.